The Determinants of Income Inequality in Europe: Do Trade Liberalisation and Financial Liberalisation Matter? - saad buba; Suryati Ishak; Muzafar Shah Habibullah; Zaleha Mohd Noor (Universitas Negeri Malang, 2019)
This study provides evidences about the determinants of income inequality in 31 sampled countries of Europe. Prior to implementing the empirical research, the study identifies the factors, which according to theories, affects the level of income inequality. Income inequality is now an issue bordering not only the developing countries, but also the emerging and the developed ones as well. The results obtained from the estimated model enabled to draw some interesting conclusions. Firstly, quality of the rule of law determines income inequality, secondly, trade liberalisation conditions income, thirdly, level of financial development determines inequality of income and finally, education level in emerging countries decreases level of income inequality, while it increases the level of inequality in the developed countries of the continent.